Implementasi Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Ponorogo - Fendik Ari Wibowo (Master of Public Administration, Universitas Slamet Riyadi, 2022)
Research background of this thesis is based on the result from the assesment of theGovernment Agencies Performance Accountability System (called: SAKIP) inPonorogo Regency by Ministry of Administrative and Bureaucratic ReformRepublic of Indonesia still getting score by “BB” category. The gorvernment of thePonorogo Regency has a target for the assesment of the Government AgenciesPerformance Accountability System in the 2020 periode will change to be Acategory. To achive the target must be supported by all Regional ApparatusOrganitation (called: OPD) in Ponorogo regency including Departement of PublicWorks and Spatial Planning. It is an responsibility for all Regional ApparatusOrganitation to get a score with the “A” or “AA” category to boost score of Government Agencies Performance Accountability System (SAKIP) in PonorogoRegency increased form “BB” to “A” category.After this research was done, it was conluded that there a need some technicalguidance and regulatioan related Government Agencies PerformanceAccountability System (SAKIP) for all the employes (ASN), as for refreshment anddeeper understanding of the implementation of Government Agencies PerformanceAccountability System (SAKIP) with the intention they can compose GovernmentAgencies Performance Accountability System (SAKIP) correctly. The separateoffice also an hamper for understanding the Government Agencies PerformanceAccountability System (SAKIP) well. The resources is not optimally yet, especiallythose who has technical background. And and there is still an inconsistencybetween the documents so that the perfection of the data is not good, its necessaryto do some document review. The success of the implementation of the Government Agencies PerformanceAccountability System (SAKIP) at Departement General Work and SpatialPlanning of Ponorogo regency which is measured according to Edward III's theoryconsists of four indicators, namely ‘communication, resources, disposition,bureaucratic structure’. Overall, the results of the research show that the ability ofthe employes (ASN) in the Departement General Work and Spatial Planning inresponding to the policy of the Government Agency Performance AccountabilitySystem (SAKIP) is already good even though not 100% of all them understanddeeply about Government Agency Performance Accountability System (SAKIP). Keywords : implementation, communication, resources, disposition,bureaucratic structure.